From defects to catalysis: mechanism and optimization of NO electroreduction synthesis of NH3 - Linling, Gan; Liao, Zhen; Zhang, Huimei; Jiang, Jinxia; Chen, Zhikai (Frontiers in Chemistry, 2024)
Ammonia (NH₃) is a crucial industrial raw material, but the traditional Haber-Bosch process is energy-intensive and highly polluting. Electrochemical methods for synthesizing ammonia using nitric oxide (NO) as a precursor offer the advantages of operating under ambient conditions and achieving both NO reduction and resource utilization. Defect engineering enhances electrocatalytic performance by modulating electronic structures and coordination environments. In this brief review, the catalytic reaction mechanism of electrocatalytic NO reduction to NH3 is elucidated, with a focus on synthesis strategies involving vacancy defects and doping defects. From this perspective, the latest advances in various catalytic reduction systems for nitric oxide reduction reaction (NORR) are summarized and synthesized. Finally, the research prospects for NO reduction to NH₃ are discussed.